2021
DOI: 10.33899/ijvs.2020.126772.1377
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular investigation of caseous lymphadenitis among the slaughtered sheep at Duhok Abattoirs; experimental infection with Corynebacterium pseudotuberculosis in rabbits

Abstract: Caseous lymphadenitis is a chronic infection caused by Corynebacterium pseudotuberculosis that affects the lymphatic system, resulting in abscesses in the lymph nodes and internal organs. This study was conducted to determine the prevalence rate of caseous lymphadenitis among slaughtered sheep in Duhok abattoirs, Duhok, Iraq and to investigate to what extend rabbits can develop caseous lymphadenitis just like that in sheep. A total of 1052 carcasses of sheep were randomly selected (939 males and 113 females) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The data found that the rates of CLA in sheep and goats were 0.94% and 1.93%, respectively. These findings are in line with prevalence rates that were reported in slaughtered goats (1.1%) at the local slaughterhouses in Elazig Province, in the east of Turkey ( Çetinkaya et al , 2002 ) and 2.4% in clinically examined goats in Rajasthan, India ( Kumar et al , 2012 ) and in line with the prevalence rate (1.93%) in sheep slaughtered in Sumel district of Duhok Province, Iraq ( Issa et al , 2021 ). Whereas, higher rates of CLA in sheep (26.3%) and goats (45.5%) were reported by Algammal (2016) in Menoufia Governorate, Egypt, and Rizk et al (2019) who reported the prevalence rate of the disease (13%) in sheep and goat in Beni-Suef Governorate in Egypt.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The data found that the rates of CLA in sheep and goats were 0.94% and 1.93%, respectively. These findings are in line with prevalence rates that were reported in slaughtered goats (1.1%) at the local slaughterhouses in Elazig Province, in the east of Turkey ( Çetinkaya et al , 2002 ) and 2.4% in clinically examined goats in Rajasthan, India ( Kumar et al , 2012 ) and in line with the prevalence rate (1.93%) in sheep slaughtered in Sumel district of Duhok Province, Iraq ( Issa et al , 2021 ). Whereas, higher rates of CLA in sheep (26.3%) and goats (45.5%) were reported by Algammal (2016) in Menoufia Governorate, Egypt, and Rizk et al (2019) who reported the prevalence rate of the disease (13%) in sheep and goat in Beni-Suef Governorate in Egypt.…”
Section: Discussionsupporting
confidence: 88%
“…However, differences in the prevalence of disease between study locations were found in terms of gender. The higher rates in females are probably due to the fact that females of sheep and goats in the study area were usually kept for s longer period than males for breeding purposes which exposes females to predisposing factors like pregnancy, shearing, and interaction with sick animals, as previously reported by Yitagesu et al (2020) and supported by Issa et al (2021) . Whereas, our data found that the prevalence rate in sheep in Sumel was significantly higher ( p < 0.01) in rams than ewes which is probably due to the intensive husbandry where rams physically interact more than ewes during the mating season, the risk of pressing on and rupturing abscesses increases.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Suspected colonies of S. aureus by traditional methods were further confirmed by the detection of the S. aureus-specific thermostable nuclease gene (nuc) by using PCR [14]. DNA was extracted according to the literature [15,16]. Briefly, a few bacterial colonies were resuspended in 500 μl of deionized doubled distilled water and mixed very well using vortex.…”
Section: Molecular Detection Of S Aureus Dna Extractionmentioning
confidence: 99%